Examining the Relevance and Philosophical Significance of Some Northern Sotho Proverbs in the Context of COVID-19: A Sociocultural Perspective - Seanego, James (International Journal of Membrane Science and Technology, 2023)
Proverbs have long been serving as a tool for shaping human being’s life. They serve as a philosophical tool for social cohesion among other socio-cultural significances. Though some critics regard them as ancient, proverbs are still fulfilling the philosophical purpose(s) in the COVID-19 era. Their philosophical nature and meaning remains relevant in many contemporary life occurrences. Observing how people self-conduct themselves and share information about the pandemic, it was imperative for the study of this nature to be documented to ease communication among people during and post the pandemic. It is against this backdrop that this paper aimed at contextualising the meaning(s) of some Northern Sotho proverbs in the COVID-19 epoch and examine how they are relevant to the pandemic’s situation and happenings. Qualitative research approach undergirded this study in the sense that the relevance of traditional Northern Sotho proverbs is tested against the global status quo (COVID-19 times). The study adopted Vygotsky’s (1978) Sociocultural theory as its lynchpin to enable a critical and thorough examination and assessment of the importance of language (through proverbs) in the COVID-19 context. Relevant Northern Sotho proverbs were purposively selected due to their significant role in the COVID-19 epoch. The proverbs were synthesised and analysed thematically to reveal their relevance and philosophical purpose during and post the pandemic. The study ultimately argues that language, through proverbs as its fundamental aspects and ideological tools, remains a major philosophical source of communication among living folks.